Letter from Chizuko Iwanaga to Ken Kitasako, Secretary of San Luis Obispo Buddhist Church - Chizuko Iwanaga::::::author::: (1927)
A notice from Chizuko Iwanaga to Ken Kitasako that U.S. customs cleared the shipment of the Obutsudan for the San Luis Obispo Buddhist Church. As the letter states, "I am very happy to inform you that the Bill of Lading finally came, and your Obutsudan shipments have all been cleared through Customs and are already enroute via Pacific Motor Transport. / Through the efforts of Mr. Charles Yonezu, everything was cleared without any custom duties. According to U.S. Custom Regulations, the Obutsudan is duty-free, but all accessories as listed in your invoice are dutiable. But through his many direct contacts with the two Customs Inspectors and after much difficulties, they were passed with no custom duties. Otherwise, the custom duties would have been quite high. / The $12.80 on the bill enclosed is a bottle of whiskey each to the two Custom Inspectors. The brokerage charge of $10.50 has been cut to half of the regular fee. / I feel that a letter of thanks to Mr. Charles Yonezu will be greatly appreciated. / With many best wishes on your NYUBUTSUSHIKI, I wish to remain / Yours truly in Gassho, [signed]".